2018
DOI: 10.1111/jbg.12350
|View full text |Cite
|
Sign up to set email alerts
|

Expected consequences of including methane footprint into the breeding goals in beef cattle. A Spanish Blonde d'Aquitaine population as a case of study

Abstract: This study evaluates two potential scenarios for including methane (CH ) emissions in the breeding objectives of beef cattle, using the Spanish population of Blonde d'Aquitaine as a case of study. First, CH emissions were included as a cost using a shadow carbon price of 1.22€/CH kg (0.044€/CO kg) (carbon tax scenario). In the other scenario, a CH quota was applied, optimizing emissions per unit of product. The current production system was used as benchmark scenario (Scenario 1). The economic value of CH was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Methane is not only an environment-related trait, it is also associated with feed efficiency, because enteric methane is not transformed into metabolized energy for the animal and is exhaled to the atmosphere, with a subsequent feeding cost for the producer (Johnson and Johnson, 1995). Several authors have proposed incorporating environment-related traits, mainly methane production, into breeding goals (Bell et al, 2016;Amer et al, 2018;López-Paredes et al, 2018). Measuring methane on farms requires less infrastructure than other feed efficiency-related traits (e.g., feed intake).…”
Section: Introductionmentioning
confidence: 99%
“…Methane is not only an environment-related trait, it is also associated with feed efficiency, because enteric methane is not transformed into metabolized energy for the animal and is exhaled to the atmosphere, with a subsequent feeding cost for the producer (Johnson and Johnson, 1995). Several authors have proposed incorporating environment-related traits, mainly methane production, into breeding goals (Bell et al, 2016;Amer et al, 2018;López-Paredes et al, 2018). Measuring methane on farms requires less infrastructure than other feed efficiency-related traits (e.g., feed intake).…”
Section: Introductionmentioning
confidence: 99%
“…Bell et al (2016) estimated the economic value of methane in the UK at −£1.68/kg of CH 4 (≃€1.77/kg of CH 4 ). López-Paredes et al (2018) formulated a similar bio-economic model that included CH 4 emissions in the breeding goal in beef cattle, resulting in an economic value from −€0.16 to −€0.54/kg of CH 4 /calf per year for cows and from −€0.34 to −€1.22/kg of CH 4 /calf per year for calves in a feedlot. In this study, we proposed scenarios that serve as theoretical situations in which exhaled CH 4 is considered in the breeding goal, either as a direct carbon tax or as a waste of energy exhaled by the cow.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock farming is responsible for 13% of global greenhouse gas (GHG) emissions (Leip et al, 2010); in particular, methane emission is an important contributor because it has a global warming potential 28 times greater than that of CO 2 (Myhre et al, 2013). Ruminants are considered one of the most important sources of global CH 4 emissions from livestock, producing around 4,623 Mt of CO 2 equivalents (CO 2 e) per year, with dairy cattle being responsible for 2,128 Mt of CO 2 e per year (Gerber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, care must be taken when including MeP in the breeding goal, that reductions are not achieved by breeding for smaller and low-milkproducing cows. Likewise, Lopez-Paredes et al (2018) concluded that a carbon quota scenario (that included CH 4 ) would select smaller cows and consequently lower CH 4 emissions in a study that measured expected consequences of including CH 4 footprint into the breeding goal of beef cattle. Additionally, it is important to mention that in the indexes 1 and 2 the reduction of MeP is only a reduction in the expected gain, given that the values are positive, and it is only by including RMet that a real reduction (negative values) is achieved.…”
Section: Correlated Responses When Including Methane In the Selection Indexmentioning
confidence: 99%